2001
DOI: 10.1139/cjpp-79-11-932
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain stimulates unidirectional and net potassium efflux in resting mammalian skeletal muscle

Abstract: The present study compared ouabain-sensitive unidirectional K+ flux into (JinK) and out of (JoutK) perfused rat hindlimb skeletal muscle in situ and mouse flexor digitorum brevis (FDB) in vitro. In situ, 5 mM ouabain inhibited 54 +/- 4% of the total JinK in 28 +/- 1 min, and increased the net and unidirectional efflux of K+ within 4 min. In contrast, 1.8 mM ouabain inhibited 40 +/- 8% of the total JinK in 38 +/- 2 min, but did not significantly affect JoutK. In vitro, 1.8 and 0.2 mM ouabain decreased JinK to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For experiments with ouabain, an appropriate volume of the ouabain stock solution was added to perfusate plasma to give 5 mM ouabain. While concentrations of 1 mM have typically been used in studies using intact skeletal muscle [22], we have found that 5 mM ouabain provides a more rapid and pronounced inhibition of JinK than 1 mM ouabain, with no known non-specific effects [23]. The final arterial perfusate DMSO concentration from all DMSO-containing solutions did not exceed 0.8%.…”
Section: Perfusatementioning
confidence: 78%
See 2 more Smart Citations
“…For experiments with ouabain, an appropriate volume of the ouabain stock solution was added to perfusate plasma to give 5 mM ouabain. While concentrations of 1 mM have typically been used in studies using intact skeletal muscle [22], we have found that 5 mM ouabain provides a more rapid and pronounced inhibition of JinK than 1 mM ouabain, with no known non-specific effects [23]. The final arterial perfusate DMSO concentration from all DMSO-containing solutions did not exceed 0.8%.…”
Section: Perfusatementioning
confidence: 78%
“…Cellular shrinkage or membrane depolarization may have resulted in the transient opening of mechanosensitive or voltage-gated K + channels, allowing K + to flow down its chemical gradient. Clearly, these channels would have to be relatively insensitive to barium, and the use of barium also rules out the likelihood of K + efflux through voltage-gated Na + channels noted previously in ouabain-treated muscles [23].…”
Section: Role Of the Nkcc In Skeletal Muscle Cell Volume Regulationmentioning
confidence: 99%
See 1 more Smart Citation